Cihapit Market Tourism Development Potential in Bandung City: a Strategic Analysis Based on Tourist Perceptions and Preferences - Annisa Nurul Syahidah; Arief Fadhillah; Shafira Nur Azizah (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The city of Bandung has a variety of interesting tourist attractions, both in terms of culture, history, and visitor experience. One location with the potential to be developed as a tourist destination is Cihapit Market, a traditional market that combines trading activities, social interaction, and the historical value of the city. This study aims to identify the potential for developing Cihapit Market as a tourist destination based on tourist perceptions and preferences. The method used is quantitative descriptive, with data collection through questionnaires to 40 visitor respondents, location observation, and interviews. The results show that the main identity of Cihapit Market is as a culinary tourist destination, with 95.0% of respondents stating that culinary is their main purpose of visit. This market has a strong loyalty base, with 60.0% of respondents recorded as repeat visitors, and promotion is strongly supported by social media channels (75.0%). Respondents' perceptions of the atmosphere and sense of security in the market are also relatively high. However, this potential is overshadowed by accessibility challenges: 82.5% of respondents are highly dependent on private vehicles (motorcycles and cars), which leads to low perceptions of parking availability and management (average score of 3.25). Another weakness is the need to improve public facilities such as cleanliness, sanitation, and toilets. The strategic recommendations proposed include improving infrastructure (parking and cleanliness), strengthening collaborative governance with the city government, developing authentic cuisine that favors the local community, and strengthening event-based promotion through social media. The implementation of these recommendations aims to make Cihapit Market a sustainable and competitive tourist destination.